Molecular epidemiology of Giardia and Cryptosporidium among outpatients in Sana’a City, Yemen / Naelah Abdulaziz Alyousefi - Alyousefi, Naelah Abdulaziz (2012)
Giardia and Cryptosporidium are two common causative agents of protozoan infections in developed and developing worlds. Currently, there is insufficient information on the molecular epidemiology of these protozoa in Yemen. This study was conducted to identify the molecular epidemiology of these two protozoan parasites by evaluating the risk factors that contribute towards understanding the possible role of transmission of these protozoa among Yemeni patients. Samples were collected from September 2008 to March 2009. All information were gathered using a standard pre-tested questionnaire; permissions were obtained from the heads of every hospital and patients were randomly and voluntarily selected. In case of children, permissions were obtained from parents. On the same day of collection, parasitic identification was done directly by microscopy after formal ether concentration technique. The modified Ziehl-Neelsen stain was used to identify oocyst of Cryptosporidium. A total of 503 samples was collected, all samples were preserved for molecular genotype using potassium dichromate. The microscopy work was carried out in Yemen, while the molecular genotyping was done at Department of Parasitology, Faculty of Medicine, University of Malaya, Malaysia. The overall prevalence of intestinal protozoan infections was 30.9%. Infection rates of Giardia duodenalis, Entamoeba histolytica/dispar and Cryptosporidium were 17.7%, 17.1% and 1%, respectively. Other parasites detected included Ascaris lumbricoides (2.4%), Schistosoma mansoni (0.3%), Hymenolepis nana (1.4%) and Enterobius vermicularis (0.4%). Multivariate analysis using forward stepwise logistic regression based on intestinal protozoan infections showed that contact with animals (OR = 1.748, 95% CI = 1.168–2.617) and taking bath less than twice a week (OR = 1.820, 95% CI = 1.192–2.779) were significant risk factors of protozoan infections. Molecular analysis of Giardia targeted the genotyping of 16S rRNA gene and subgenotyping of b-giardin genes. For Cryptosporidium, the 18S rRNA and gp60 genes were used for genotyping and subtyping respectively. Of the 89 microscopic positive Giardia samples, 65 were successfully sequenced, of which 43 (66%) were identified as Giardia duodenalis assemblage A and 22 (34%) as G. duodenalis assemblage B. The subtyping analysis based on b-giardin gene identified the presence of G. duodenalis assemblages A2, A3 and B3. Infections with assemblage A were significantly associated with animal contact (P < 0.05) and grass collection activity for animal feed (P < 0.05). For Cryptosporidium species, out of 335 samples that were randomly chosen for DNA extraction, 33 (9.9 %) were positive. Of these, 33 (96%) were identified as C. parvum whilst one case was caused by C. hominis. All seven C. parvum isolates subtype belonged to the IIaA15G2R1 subtype. The predominance of the zoonotic IIa subtype family of C. parvum highlights the likely occurrence of zoonotic transmission of cryptosporidiosis in Yemen. In conclusion, the present study on protozoan diseases indicated that low personal hygiene and contact with animals were important predictors for intestinal protozoan infections. Data of the study based on molecular work suggest that both anthroponotic and zoonotic transmissions play potential roles in the transmission of giardiasis in the community. However, this postulation needs confirmation with future molecular epidemiological studies in both humans and animals. The findings on risk factors combined with molecular genotyping will assist in developing effective control strategies in Yemen based on a better understanding of epidemiology of this parasite. The findings also warrant further genotyping studies among animals. In order to effectively reduce these infections, a multi-sectoral effort is needed including preventive measures such as good hygienic and animal husbandry practices, heightened provision of educational health programs and health services in all governorates including rural areas. Furthermore, it is also essential to find radical solutions to the recent water crises in Yemen.